Performance of Sweet corn (Zea mays L. var. saccharata Sturt) under varying fertility levels in summer season - Chouhan, Bhagwat Singh; jadhav, K.V.; Singh, Bahadur; Singh, Shailendra; Kunwar, Pushpa (Annals of Agricultural Research, 2016)
A field experiment was conducted at Junagadh during summer season of 2011 to work out optimum fertilizer dose and evaluate production potential of summer sweet corn. The treatment consisted of combination of 4 nitrogen levels (0, 60, 120 and 180 kg N ha–1) and 4 phosphorus levels (0, 30, 60 and 90 kg P2O5 ha–1). Significant increase in green cob yield and green fodder yield was found under higher dose. The highest green cobs yield, green fodder yield and other yield attributes and nutrient uptake obtained under 180 kg N ha–1. Application of 90 kg phosphorus ha–1 significantly increased green cob yield and green fodder yield. Application of 120 kg N ha–1 and 60 kg P2O5 ha–1 proved to be more economic viable in view of its higher net return and benefit: cost ratio over rest combination for higher productivity (5431 kg ha–1) and profitability (Rs 51656 ha–1 net return).